A modular approach to HIV-1 proteinase inhibitor design - Uhlíková, T; Konvalinka, J; Pichová, I; Soucek, M; Kräusslich, H G; Vondrásek, J (Biochemical and biophysical research communications, 1996)
HIV-1 proteinase represents a promising target for antiviral chemotherapy. We have designed, synthesized, and tested modular inhibitors combining an active-site inhibitor tethered to a structure targeted to the dimerization domain of the enzyme. At pH 5 the parent active site inhibitor, the equimolar mixture of active site and dimerization inhibitors, and the best compound from our series of modular inhibitors show the same inhibition activity. At neutral pH, however, the combination of the dimerization and active-site inhibitors shows a synergistic effect. Moreover, the modular inhibitor has an IC50 value 5x lower than the parent active site inhibitor and 2x lower than the equimolar mixture of the two parent inhibitors. The Lineweaver-Burk plot for modular inhibitors corresponds to a pattern for mixed type inhibition.
Keywords: Protein Binding; inhibitory HIV-proteasy; HIV-1; vazebná místa; Structure-Activity Relationship; racionální návrh léčiv; molekulární sekvence - údaje; Amino Acid Sequence; Hydrogen-Ion Concentration; HIV Protease Inhibitors; vztahy mezi strukturou a aktivitou; koncentrace vodíkových iontů; vazba proteinů; Binding Sites; kinetika; HIV Protease; HIV-proteasa; Peptides; sekvence aminokyselin; Drug Design; peptidy; Molecular Sequence Data; Kinetics